Safety of beta-alanine supplementation in humans: a narrative review - de Oliveira, E. P.; Artioli, G. G., Burini, R. C. (Sport Sciences for Health, 2023)
Carnosine levels play a significant role in intracellular pH buffering during exercise. The limiting factor for muscle carnosine synthesis is the availability of ß-alanine. Results from meta-analysis showed a significant positive effect of ß-alanine supplementation on high-intensity exercise performance. Nonetheless, much less has been described about the safety of ß-alanine. The available literature indicates no adverse events related to ß-alanine usage; side effects such as paresthesia may be observed if a large single high dose of ß-alanine is taken, but the symptom can be attenuated either by using splitting doses (< 1.6 g) or a sustained-release formula. No adverse effects have been reported up to 24 weeks of ß-alanine supplementation (3.2 g.day-1), but the adverse effects of longer supplementation periods are still unknown. Most of the existing clinical studies were not designed with safety evaluations as primary end points. ß-Alanine is currently considered to be safe in healthy populations, at recommended doses, by the International Society of Sports Nutrition stands position, while the Australian Institute of Sports has established ß-alanine as a safe performance-enhancing supplement with strong scientific evidence (grade A). Cohort studies are needed evaluating the safety of ß-alanine among representative populations, and the effects of co-variables such as sex, age, and ethnicity.